Influencers to Firm Value: Does Tax Avoidance Plays a Mediating Role? - Syura, Asy; Arfan, Muhammad; Anzib, Nuraini (Jurnal ASET (Akuntansi Riset), 2020)
This study aims to examine tax avoidance as a mediation effect of corporate governance, financial leverage and sales growth on firm value. The four exogenous variables will be tested for their effect on one endogenous variable, which is firm value. This research is a census research, which includes all manufacturing companies which are the population in the observation of 55 companies. The observation period of research data is 2016-2018. The analytical method used is path analysis. The results of this study found that corporate governance, financial leverage and sales growth affect the value of the company. Tax avoidance fully mediates the effect of corporate governance on corporate value. Whereas tax avoidance partially mediates the effect of financial leverage and sales growth on firm value.